KAPASITAS PEMERINTAH DESA SARDONOHARJO KABUPATEN SLEMAN DALAM IMPLEMENTASI PENGELOLAAN DANA DESA TAHUN 2021 - Jefri Davidson Ama Sabon; Hanantyo Sri Nugroho (Jurnal Partisipatoris, 2023)
This research examines the capacity of the Sardonoharjo village government in implementing village fund management during the pre-pandemic and Covid-19 pandemic era. To study this problem, researchers used implementation theory according to Van Meter and Van Horn. This study uses descriptive qualitative methods and researchers act as research instruments. Data obtained through observation, interviews, and documentation studies. The results of this study indicate that village fund management, in the government of Sardonoharjo village before the Covid-19 pandemic, prioritized the use of village funds for village strategic program activities that were cross-sectoral in nature. The activity program is both physical and non-physical development. For physical development, the Sardonoharjo Village government focuses on repairing and maintaining infrastructure for the most basic needs of village communities, such as water irrigation, roads, lighting, village economic stalls, agricultural business development, while non-physical programs or activities The Sardonoharjo Village Government prioritizes service program activities that are basic services. which directly brings benefits to improving the economy and quality of life of village communities such as public health, improving the economy through the development of superior village products, and others. before the Covid-19 pandemic, the use of village funds during this pandemic was used for non-physical program activities, while development activities of a physical nature were abolished which focused on the economic recovery of rural communities, in the form of providing direct village cash assistance (BLT), and revitalizing village-owned enterprises.